Predictive value of biomarkers for the prognosis of acute pulmonary embolism in Japanese patients: Results of the Tokyo CCU Network registry - Tanabe, Yasuhiro; Obayashi, Toru; Yamamoto, Takeshi; Takayama, Morimasa; Nagao, Ken (Journal of cardiology, 2015)
Several studies from Western countries have reported associations between cardiac troponin and B-type natriuretic peptide (BNP) levels and acute pulmonary embolism prognosis; however, the number of such reports from Asian countries, including Japan, is limited. Thus, we evaluated the relationship between blood biochemical findings and acute-phase pulmonary embolism prognosis in Japanese patients. The subjects included 441 patients with acute pulmonary embolism (191 men, 250 women; average age, 65.8±16.0 years) treated at Tokyo CCU Network Institutions from 2009 to 2011 and registered via survey forms. The association between blood biochemical findings at admission and 30-day mortality was investigated. The median BNP value was 186.5pg/mL (25th to 75th interquartile range: 49.8–500pg/mL) of 210 cases. No deaths were recorded among those with BNP levels <90pg/mL (n=70), whereas significantly higher mortality (10 deaths/140 cases, 7.1%; p=0.033) was observed among those with BNP levels ≥90pg/mL. A qualitative cardiac troponin test was positive in 58 of the 204 cases (28.4%), with a significantly higher mortality incidence (p=0.017) among the troponin-positive cases [6 (10.3%) versus 3 (2.1%) deaths among the 146 troponin-negative cases]. The overall mean blood glucose level at admission of 331 cases was 152.0±74.0mg/dL, and 30-day mortality significantly increased with blood glucose values (p=0.048). Troponin, BNP, and blood glucose levels are useful prognostic biomarkers for acute pulmonary embolism in Japanese patients.